Дифференцирование сингулярных интегралов с кусочно-непрерывной плотностью и граничные значения производных интеграла типа Коши - Плакса, С.А. (Український математичний журнал, 2005)
Встановлено достатні умови для диференційовності сингулярного інтеграла Коші з кусково-неперервною щільністю. Одержано формули для похідних порядку n сингулярного інтеграла Коші та для граничних значень похідних порядку n інтеграла типу Коші. We establish sufficient conditions for the differentiability of a singular Cauchy integral with piecewise-continuous density. Formulas for the nth-order derivatives of a singular Cauchy integral and for the boundary values of the nth-order derivatives of a Cauchy-type integral are obtained.